2019
DOI: 10.7554/elife.40981
|View full text |Cite
|
Sign up to set email alerts
|

The elemental mechanism of transcriptional pausing

Abstract: Transcriptional pausing underlies regulation of cellular RNA biogenesis. A consensus pause sequence that acts on RNA polymerases (RNAPs) from bacteria to mammals halts RNAP in an elemental paused state from which longer-lived pauses can arise. Although the structural foundations of pauses prolonged by backtracking or nascent RNA hairpins are recognized, the fundamental mechanism of the elemental pause is less well-defined. Here we report a mechanistic dissection that establishes the elemental pause signal (i) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 70 publications
(176 reference statements)
17
89
0
Order By: Relevance
“…We believe that this might be the reason behind our observation regarding the limited effect of GreB on the averege backtracking durations. These findings are consistent with (20,51).…”
Section: Average Backtracking Durations Show Little Change In the Presupporting
confidence: 92%
“…We believe that this might be the reason behind our observation regarding the limited effect of GreB on the averege backtracking durations. These findings are consistent with (20,51).…”
Section: Average Backtracking Durations Show Little Change In the Presupporting
confidence: 92%
“…In E. coli, a special pausing signal G-10Y-1G+1 (Y-1 represents the pause site) was identified [5][6][7] , which slows down RNA polymerase (RNAP) near a translation start site allowing coordination of RNAP movement with cotranscriptional translation. The elemental pause could be further stabilized by an RNA hairpin formed in the RNA exit channel of RNAP 8,9 or by RNAP backtracking 10,11 . During backtracking, RNAP moves backward along the DNA and the nascent RNA leading to extrusion of the RNA 3' end into the RNAP secondary channel to induce long pause or transcription arrest 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of 2 μM of GreA completely abolished the OZM induced arrest at +7 suggesting that the arrest was predominantly due to backtracking. While the consensus pause is known to be fractionally backtracked, GreA does not speed up the RNAP escape from the consensus pause site (96,98). We concluded that the pause sequence most likely solely provided time for the TEC to backtrack but was not itself a rate limiting step for the recovery from the OZM-induced arrest.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our data suggested that OZM arrested transcription exclusively by promoting backtracking. While the consensus-pause-like sequence was involved in arresting RNAP in one case, the alleviation of the arrest by GreA suggested that the escape from the pause was not rate limiting (96,98), and that the pause merely provided time for entry into the backtracked state by a fraction of the transcribing RNAP. Noteworthy, a synthetic pyrazine-carboxamide nucleotide analog T-1106 has been recently suggested to inhibit viral RNA-dependent RNA polymerase by promoting backtracking (99).…”
Section: Discussionmentioning
confidence: 99%